2008
DOI: 10.1258/jms.2008.008069
|View full text |Cite
|
Sign up to set email alerts
|

Normal endometrial cells in cervical cytology: systematic review of prevalence and relation to significant endometrial pathology

Abstract: Compared with conventional cytology, LBC may be associated with a higher prevalence of NECs but these are less likely to be associated with endometrial pathology. This finding might be explained by more consistent use of sampling instruments for LBC with better access to the endocervical canal or alternatively by changes over time, broadly coincident with the introduction of LBC, in the population in which NECs are reported. In followed-up women with NECs, most endometrial pathology is accompanied by symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although mass screening program is not designed to detect endometrial carcinoma, early detection of such cases has benefit for involved asymptomatic patients 8 . In one study 48% of endometrial carcinoma preceded abnormal cervico‐vaginal cytology 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Although mass screening program is not designed to detect endometrial carcinoma, early detection of such cases has benefit for involved asymptomatic patients 8 . In one study 48% of endometrial carcinoma preceded abnormal cervico‐vaginal cytology 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…However, the various studies published since 1970 shows were listed below-( The reported prevalence of normal endometrial cells in all smears varied between 0.1% to 1.4% [38] and Atypical glandular cells ranging from 0.18 to 0.74% [39], [40] The increased prevalence of endometrial cells in our study may be because of confinement of patients selection was only from bleeding history cases in which some pathology must be there. The presence of endometrial glandular cells was found to indicate a five times greater risk of endometrial disease [41].…”
Section: Discussionmentioning
confidence: 89%
“…Recently a meta-analysis determined that a TVUS result of 5 mm or less reduces the risk of endometrial cancer by 84%. 6,10 In Some cases, it is recommended that hysteroscopy and endometrial sampling should be done if clinical suspicion is higher. 1,11 In the women with diabetes mellitus and obesity has been difficult to the assessing endometrial thickness, but models has been planned to take personal characteristics into account when predicting the risk of malignancies.…”
Section: 31mentioning
confidence: 99%
“…A major growth may be need direct referral to 'one stop' specialist clinics. 10,11,6,30 In advance clinical practices, various investigating tools are available to provide clinical evaluation, including ultrasound, hysteroscopy and endometrial sampling techniques like pippelle.…”
Section: 31mentioning
confidence: 99%